Sex differences in depolarizing actions of GABAA receptor activation in rat embryonic hypothalamic neurons - Mir, Franco Rafael (2017)
GABAA receptor activation exerts trophic actions in immature neurons through depolarization of resting membrane potential. The switch to its classical hyperpolarizing role is developmentally regulated. Previous results suggest that a hormonally biased sex difference exists at the onset of the switch in hypothalamic neurons. The aim of this work was to evaluate sex differences in GABAA receptor function of hypothalamic neurons before brain masculinization by gonadal hormones. Hypothalamic cells were obtained from embryonic day 16 male and female rat foetuses, 2 days before the peak of testosterone production by the foetal testis, and grown in vitro for 9 days. Whole-cell and perforated patch-clamp recordings were carried out in order to measure several electrophysiological parameters. Our results show that there are more male than female neurons responding with depolarization to muscimol. Additionally, among cells with depolarizing responses, males have higher and longer lasting responses than females. These results highlight the relevance of differences in neural cell sex irrespective of exposure to sex hormones.